Synthesis and Characterization of New N-acyl Hydrazone Derivatives of Carprofen as Potential Tuberculostatic Agents - Ilinca Margareta Vlad; Diana Camelia Nuță; Miron Theodor Căproiu; Florea Dumitrașcu; Eleonóra Kapronczai; Georgiana Ramona Mük; Speranta Avram; Adelina Gabriela Niculescu; Irina Zarafu; Vanesa Alexandra Ciorobescu; Ana Maria Brezeanu; Carmen Limban (MDPI AG, 2024)
N-acyl hydrazone (NAH) is recognized as a promising framework in drug design due to its versatility, straightforward synthesis, and attractive range of biological activities, including antimicrobial, antitumoral, analgesic, and anti-inflammatory properties. In the global context of increasing resistance of pathogenic bacteria to antibiotics, NAHs represent potential solutions for developing improved treatment alternatives. Therefore, this research introduces six novel derivatives of (EZ)-N'-benzylidene-2-(6-chloro-9H-carbazol-2-yl)propanehydrazide, synthesized using a microwave-assisted method. In more detail, we joined two pharmacophore fragments in a single molecule, represented by an NSAID-type carprofen structure and a hydrazone-type structure, obtaining a new series of NSAID-N-acyl hydrazone derivatives that were further characterized spectrally using FT-IR, NMR, and HRMS investigations. Additionally, the substances were assessed for their tuberculostatic activity by examining their impact on four strains of M. tuberculosis, including two susceptible to rifampicin (RIF) and isoniazid (INH), one susceptible to RIF and resistant to INH, and one resistant to both RIF and INH. The results of our research highlight the potential of the prepared compounds in fighting against antibiotic-resistant M. tuberculosis strains.